Factors Influencing Financial Management Behavior Among Millennials & Gen Z Using Online Loans in Surabaya - Akmal Wibowo; Trias Madanika Kusumaningrum (Lavish Opulent Education, 2025)
Financial behavior emerged around 1990. In Indonesia, consumer behavior causes low savings. Online loans, supported by technology, are rampant with easy access. Surabaya, a metropolitan city with high fintech activity, recorded many borrowers and complaints of online loans. Generation Z and Millennials (19-34 years) are the largest users of online loans, often for lifestyle, with a credit value reaching IDR 26.87 trillion. Ease of digital access encourages consumption and use of online loans among this generation. This study uses quantitative research techniques, Quantitative research is a positive-based research approach. This approach is used to analyze the population and samples studied. Data analysis is carried out statistically or with measurable measures to check the assumptions that have been set. The study shows that financial literacy, financial self-efficacy, and financial attitude have a positive effect on the financial management behavior of the Millennial and Z generations who use online loans. However, lifestyle has a negative effect. The level of financial literacy, financial self-efficacy, and financial attitude of respondents is relatively high, while lifestyle is also high. Oddly enough, income does not have a significant effect on their financial management behavior. financial literacy, financial self-efficacy, and financial attitude positively influence the financial management behavior of Millennial and Z generations of online loan users in Surabaya. However, a consumptive lifestyle has a negative effect. Oddly enough, income does not significantly influence their financial behavior, because other factors such as literacy and lifestyle are more dominant.